1982
DOI: 10.1099/0022-1317-63-2-457
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Rotavirus Antigens in Infected Cells by Ultrastructural Immunocytochemistry

Abstract: SUMMARYVirus structural antigens were localized within a line of monkey kidney (MA104) cells infected with the simian rotavirus SA11 using electron microscopic immunoperoxidase techniques. When hyperimmune guinea-pig anti-SA11 serum was used, virus particles, membranes of virus-associated endoplasmic reticulum, and viroplasmic inclusions were most heavily labelled. A general cytoplasmic reaction (ribosomes, intracytoplasmic membranes, etc.) with anti-SA 11 serum was also observed, but nuclei were unstained. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 15 publications
3
65
1
Order By: Relevance
“…Since the nucleocapsid protein constitutes approximately 80 ~ of the protein in single-shelled particles, the arrangement of this protein has been the focus of many studies (Chasey & Labram, 1983;Martin et al, 1975;Palmer et al, 1977;Palmer & Martin, 1982;Petrie et al, 1982;Sabara et aL, 1985). Electron microscopical examination of virus particles suggested the arrangement of inner capsid subunits into an open mesh exhibiting a regular pattern of holes (Martin et al, 1975).…”
Section: -7305 © 1987 Sgmmentioning
confidence: 99%
“…Since the nucleocapsid protein constitutes approximately 80 ~ of the protein in single-shelled particles, the arrangement of this protein has been the focus of many studies (Chasey & Labram, 1983;Martin et al, 1975;Palmer et al, 1977;Palmer & Martin, 1982;Petrie et al, 1982;Sabara et aL, 1985). Electron microscopical examination of virus particles suggested the arrangement of inner capsid subunits into an open mesh exhibiting a regular pattern of holes (Martin et al, 1975).…”
Section: -7305 © 1987 Sgmmentioning
confidence: 99%
“…NSP2 and NSP5, are localized (Petrie et al, 1982(Petrie et al, , 1984Welch et al, 1989). These discrete structures are found in the cytoplasm at 2-3 h post-infection (p.i.…”
Section: Introductionmentioning
confidence: 99%
“…Viroplasms are composed of viral RNA and the proteins VP1, VP2, VP3, VP6, NSP2, and NSP5 (Petrie et al 1982, Gallegos & Patton 1989, and while virion assembly occur in these structures (Petrie et al 1982, Gallegos & Patton 1989) the mechanism of viroplasms formation is unknown. Recently, it was reported that the number of rotavirus viroplasms decrease with post-infection time (Eichwald et al 2004), and while the diameter of single viroplasms increased with time, the total number of viroplasms per cell diminishes, suggesting that growth of these inclusion bodies occur by fusion and probably also by stepwise addition of viral components to the viroplasms surface (Eichwald et al 2004).…”
mentioning
confidence: 99%